Increasing shelf life of Dragon fruit by maintaining at optimum temperature - Singh, Neelima; Banjare, Praveen; Mondloe , Dilbag (Journal of Postharvest Technology, 2021)
Since fruits and vegetables are highly perishable, we must store them at a specific temperature. Because of the high field heat trapped in it and the higher moisture content, the rate of transpiration is also very high, and because they are living commodities, they undergo respiration. This generates a significant amount of heat as well as ethylene. Ethylene is a ripening hormone that aids in the ripening of fruits. As a result of these metabolic changes, fruits ripen quickly and spoil. The aim of this paper is to keep fruit from spoiling by storing it at the proper temperature. The aim of this study is to prolong the shelf life of Dragon fruit by ensuring that it is stored at the proper temperature. The dragon fruit is held at three different temperatures for this experiment, and the variations in Brix percent observed over time are analyzed. After a 24- day experiment, an optimum temperature of 4°C (1°C) was revealed, which provided the best quality fruit with the best colour and taste retention. Furthermore, there is no nutritional deficit.